Pelatihan Pembuatan Sabun Padat dari Minyak Goreng Sawit di RW 09 Kelurahan Ngadirejo Kecamatan Kartasura, Sukoharjo - Septiawan, Ponco Adi; Candra Wardhani, Novia Sagita; Tri Syafa'ati, Febriana; Rini, Setia; Hanifah, Salma; Mutiara Pratiwi, Triana; Ananda Rizki, Fadhia; Kartika Putri, Hanifah; Syawal, Raihan; Bintang Azhar, Ariq; Rahmat, Rahmat (Society : Jurnal Pengabdian Masyarakat, 2024)
With so much pollution that can cause various diseases, the need for cleaning supplies such as soap is also increasing. Good quality soap is determined by the raw materials used. Palm oil is a potential raw material for soap production. This is because lauric acid and vitamin E, which come from plants and function as antioxidants, are found in palm oil. Therefore, the community needs to be introduced to creative/innovative ideas to support government activities. One of them is PHBS (Clean and Healthy Lifestyle) in the community by introducing the manufacture of bar soap made from cooking oil which is easy to make and practiced as a form of awareness of community hygiene where there is no need to buy soap because it can be made yourself at an affordable price. RW 09 in the Ngadirejo Kartasura Village is the right target for community service because it is in a dense, busy, active area with lots of routine activities and many people who have businesses and have potential. The aim of this training was to engage local community groups with the ability to make their own bar soap. The implementation method is participatory coaching through the learning by doing method so that it is true that the people's group has been able to create the product. The results of the training showed that the training participants were able to mix 500 grams of palm cooking oil, 65 grams of NaOH, and 155 grams of Aquades water using a measuring cup to get solid bar soap and good results. Community creativity development training uses a touch of packaging innovation so that products sell well in the market and can be a follow-up to the next community service.